2004
DOI: 10.1007/s11103-004-5920-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fructose-bisphosphate aldolase regulated by gibberellin in roots of rice seedling

Abstract: Fructose-bisphosphate aldolase is a glycolytic enzyme whose activity increases in rice roots treated with gibberellin (GA). To investigate the relationship between aldolase and root growth, GA-induced root aldolase was characterized. GA3 promoted an increase in aldolase accumulation when 0.1 microM GA3 was added exogenously to rice roots. Aldolase accumulated abundantly in roots, especially in the apical region. To examine the effect of aldolase function on root growth, transgenic rice plants expressing antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 33 publications
0
77
0
Order By: Relevance
“…Therefore, an increase and/or activation of aldolase appears to be implicated in growth mainly through the promotion of ATP synthesis in the glycolytic pathway. The involvement of FBP aldolase in cell growth was identified in rice roots treated with gibberellin [26]. In this study, FBP aldolase showed down-regulation under either chilling conditions or upon BR treatments (Fig.…”
Section: Protein Identifications and Putative Functions In The Br-medmentioning
confidence: 49%
“…Therefore, an increase and/or activation of aldolase appears to be implicated in growth mainly through the promotion of ATP synthesis in the glycolytic pathway. The involvement of FBP aldolase in cell growth was identified in rice roots treated with gibberellin [26]. In this study, FBP aldolase showed down-regulation under either chilling conditions or upon BR treatments (Fig.…”
Section: Protein Identifications and Putative Functions In The Br-medmentioning
confidence: 49%
“…In yeast, the physiological significance of this association has not been determined, and studies have yet to decipher under what conditions the interaction takes place. In plants, an association between aldolase and V-ATPase subunits was noted in rice roots following the identification of aldolase in the tonoplast fraction (Tanaka et al, 2004); VHA-A, VHA-B, and VHA-a coimmunoprecipitated with aldolase, but regulation of activity was not demonstrated (Konishi et al, 2004(Konishi et al, , 2005, and physiological relevance was also lacking for this association.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose-bisphos- phate aldorase has been reported to be GA-inducible in rice roots, and the root growth of transgenic rice expressing antisense-RNA of the aldorase was suppressed. 18) However, none of these has been reported to have specific interaction with GAs.…”
Section: Resultsmentioning
confidence: 99%